Optimization of binary zeotropic mixture working fluids for an organic Rankine cycle for waste heat recovery between centrifugal compressor stages. Issue 5 (30th January 2020) - Lin, Jingxiang; Qin, Guoliang; Yue, Han
Abstract: The organic Rankine cycle is an effective way to recover low‐temperature waste heat, and a mixture working fluid can effectively improve the performance of the organic Rankine cycle. In order to find the best pure and mixture working fluid quickly and accurately, thirteen pure working fluids and zeotropic mixtures of two of those fluids are selected to study the performance of the organic Rankine cycle, and the net power output is selected as the objective function. Through calculation and analysis, the best pinch temperature difference and evaporation temperature are determined. By calculating the approximate net power output, we find that the parameter ( k ·Δ s 5‐1 ) −1, which is determined by the physical properties of a working fluid, plays an important role in the pure working fluid optimization. In addition, the condensation temperature glide and ( k ·Δ s 5‐1 ) −1 together determine the optimized binary zeotropic mixture. As a result, R227ea and R227ea/hexane (0.98/0.02) are shown to be the optimal pure working fluid and binary zeotropic mixture. Using this mixture resulted in a net power output of 424.63 kW, which is 29.3% higher than that of the pure working fluid R227ea. Abstract : In order to recover waste heat between centrifugal compressor stages using organic Rankine cycle, this paper shows a new method for finding the best binary zeotropic mixture working fluid.